DETERMINANTS OF PURCHASE DECISIONS AT TAMELO ROOF CAFÉ: PRODUCT QUALITY, PRICE PERCEPTION, LOCATION, PROMOTION AND PHYSICAL FACILITIES FOOD AND BEVAREGES PRODUCTS - Rahayu Lestari; Wahyu Bagus Satrio; Kumba Digdowiseiso (Jurnal Ekonomi, 2022)
This study aims to analyze the determinants of purchasing decisions at Tamelo Atap Café, which are influenced by product quality, price perception, location, promotion, and the physical facilities of food and beverage products. sources and research data using primary data obtained through distributing questionnaires; the research data was given to 100 respondents. Data collection techniques in research use purposive sampling. Data processing uses Partial Least Square (PLS) SmartPLS 3.0.Partially, the results of the study found that there was a positive but not significant influence on product quality on purchasing decisions; there is a positive and significant influence of location on purchasing decisions; there is a positive but not significant influence of price perceptions on purchasing decisions; there is a positive and significant influence of promotion on purchasing decisions; and there is a positive and significant influence of physical facilities on purchasing decisions.